Bank efficiency in the enlarged European Union - Dániel Holló; Márton Nagy (Magyar Nemzeti Bank, 2006)
This paper aims to estimate bank efficiency differences across member states of the European Union and tries to explain their causes. We show on an empirical basis that the level and spread of bank efficiency in the EU and their changes are significantly determined by characteristics of operational environment and the “conscious” behaviour of management. In the long term, through the integration of financial markets and institutions, as well as the establishment of the Single European Banking Market, the impact of advantages and disadvantages underlying the operational environment is reduced or eliminated; therefore only managerial ability is of any relevance. Our findings suggest that there is a costefficiency gap and convergence between the old and new member states, irrespective of the specifications of the model. With respect to profit efficiency, however, differences in efficiency between the two regions are only established after controlling for some major characteristics of the varying operational environments. Our study also investigates the relevance of and the correlation between accounting-based and statistics-based efficiency indicators. We conclude that the accounting based efficiency indicators are inadequate for managing heterogeneity arising from institutional and operational environments. Hence such indicators only allow limited cross-sectional comparison through time.
Keywords: F36; G15; G21; G34; 330; parametric approach; X- and alternative profit-efficiency; Fourier-flexible functional form; banking system; Bank; X-Effizienz; Schätzung; EU-Staaten